Pengaruh Tabungan Mudharabah Terhadap Minat Investasi Pada Pt. Bank Syariah Indonesia, Tbk KCP Pangkalan Brandan - Muhizar Muchtar, Muhammad Saleh, Rini Muliana Sari (Cybernetics: Journal Educational Research and Social Studies, 2022)
The focus of this study is to determine the effect of the mudharabah savings product offered by PT. Bank Syariah Indonesia, Tbk KCP Pangkalan Brandan on public interest in investing in PT. Bank Syariah Indonesia, Tbk KCP Pangkalan Brandan. This type of research is quantitative research that emphasizes statistical data analysis, with the aim of testing the established hypothesis. The source of this research data was obtained from the answers to the questionnaire given to the mudharabah savings customers of PT. Bank Syariah Indonesia, Tbk KCP Pangkalan Brandan. Processing and in this study using computer programs SPSS and Microsoft Office Excel. The data analysis in this study used validity test, reliability test, normality test, t test, r test, and simple linear regression analysis. The results of the study explain that there is a significant influence between mudharabah savings on investment interest in PT. Bank Syariah Indonesia, Tbk KCP Pangkalan Brandan. Mudharabah savings offered by PT. Bank Syariah Indonesia, Tbk KCP Pangkalan Brandan affects customer investment interest by 53% while the remaining 47%. There is a positive or in line relationship between Mudharabah Savings (X) and Investment Interest (Y) the better the mudharabah savings products offered by PT. Bank Syariah Indonesia, Tbk KCP Pangkalan Brandan, the customer's investment interest in PT. Bank Syariah Indonesia, Tbk KCP Pangkalan Brandan will be high, and vice versa if the mudharabah savings product offered by PT. Bank Syariah Indonesia, Tbk KCP Pangkalan Brandan is not good then the customer's investment interest in PT. Bank Syariah Indonesia, Tbk KCP Pangkalan Brandan will decline.